Detection of viral DNA sequences in the cerebrospinal fluid of patients with multiple sclerosis - Mancuso, Roberta; Hernis, Ambra; Cavarretta, Rosella; Caputo, Domenico; Calabrese, Elena; Nemni, Raffaello; Ferrante, Pasquale; Delbue, Serena; Clerici, Mario (Journal of medical virology, 2010)
The role of viruses in the pathogenesis of multiple sclerosis (MS) is a subject of heated debate. The presence of six different neurotropic viruses was sought, including JC virus (JCV), varicella zoster virus (VZV), human herpesvirus 6 (HHV-6), and Epstein-Barr virus (EBV), in cerebrospinal fluid (CSF) samples collected from 51 patients with MS and 30 patients with other neurological diseases. Cell-free or cell-associated viral DNA in CSF samples was detected by real-time PCR, and viral loads were determined. Magnetic resonance imaging (MRI) examinations were also performed to look for active lesions. Cell-associated JCV DNA was detected in 3 of the 51 patients with MS and in 2 of the 30 patients with other neurological disease. Cell-free JCV DNA was detected in one additional patient with MS. Cell-free VZV DNA was detected in one patient without MS, cell-free HHV-6 was detected in one patient with MS, and cell-free EBV was detected in one patient with MS. All other study patients had no detectable viral DNA in CSF samples and no double infections were found. The small percentage of patients with detectable viral DNA in CSF samples was comparable between patients with MS and those with other neurological disease, and presence of viral DNA was not a predictor of brain lesions. Additional observations suggest that cell trafficking from the periphery, rather than leakage through the blood-brain barrier, results in the transport of viruses to the CNS, where local immunosurveillance can control viral replication in immunocompetent individuals. J. Med. Virol. 82:1051-1057, 2010.